Role of physical activity for glycemic control among patients with type 2 diabetes mellitus (BIRDEM Medical Journal, 2024)
Background: Lifestyle modification and physical activity are very important parts of diabetes management. Regular physical activity has been shown to improve glycemic control through increased insulin sensitivity and glucose tolerance. The aims of this study were to assess the glycemic level and pattern of physical activity among type 2 diabetic patients. Methods: This hospital-based cross-sectional study was carried out from July 2022 to October 2022 among 305 purposively recruited diabetic patients who came to receive care at the outpatient department of a teaching hospital in Dhaka, Bangladesh. A semi-structured questionnaire was used to describe socio-demographic information. Physical activity was assessed using the validated version of international physical activity questionnaire short form/ global physical activity questionnaire (IPAQ/GPAQ). Glycemic control was measured by HbA1C report done within 120 days of the interview. Blood pressure and body mass index were also measured at the time of inclusion. The physical activity level was categorized according to IPAQ scoring protocol as high level, moderate level and low level. Chi square test was carried out to determine the association of physical activity with type-2 DM, body mass index, glycemic and blood pressure control. Statistical significance was defined as p